1985
DOI: 10.1007/bf01067049
|View full text |Cite
|
Sign up to set email alerts
|

Legal vs. quantified definitions of standards of proof.

Abstract: Three laboratory experiments were conducted to compare legal (unquantified) definitions of three standards of proof ("preponderance of the evidence," "clear and convincing evidence," and "'beyond a reasonable doubt") with quantified definitions, in which the standards of proof were expressed in probability terms (51%, 71%, and 91% probability of truth). In the first experiment, the quantified definitions had their intended effect--verdicts favoring the plaintiffs decreased as the standard of proof became stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 11 publications
4
93
3
Order By: Relevance
“…Interestingly, MacCoun (1984) found that assigned standards of proof did not have their expected effect on individual predeliberation verdict preferences. Similarly, Kagehiro and Stanton (1985) failed to find any effect of traditional verbal standard-of-proof instructions on individual mock jurors' verdicts, although they did find an effect of quantified instructions (e.g., greater than 50% for preponderance of evidence). Thus, the asymmetries shown in Table 8 illustrate that even legal standards of proof operate more like social norms than like epistemological inferences.…”
Section: The Deliberation Paradigmmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, MacCoun (1984) found that assigned standards of proof did not have their expected effect on individual predeliberation verdict preferences. Similarly, Kagehiro and Stanton (1985) failed to find any effect of traditional verbal standard-of-proof instructions on individual mock jurors' verdicts, although they did find an effect of quantified instructions (e.g., greater than 50% for preponderance of evidence). Thus, the asymmetries shown in Table 8 illustrate that even legal standards of proof operate more like social norms than like epistemological inferences.…”
Section: The Deliberation Paradigmmentioning
confidence: 96%
“…When mock juries are instructed to use the symmetrical "preponderance of evidence" standard, the asymmetry disappears. Interestingly, traditional "reasonable doubt" instructions have little effect on individual jurors' predeliberation judgments (Kagehiro & Stanton, 1985;MacCoun & Kerr, 1988;cf. Kerr et al, 1976).…”
Section: The Deliberation Paradigmmentioning
confidence: 99%
“…Wells also argued that these data cannot be explained according to the dominant decision model in this area, the probability threshold model. According to this model, "triers of fact" reason from evidence to fact; that is, they make an affirmative decision, such as liability, when the subjective probability of liability exceeds a threshold probability (e.g., Carlson & Dulaney, 1988;Connolly, 1987;Dane, 1985;Kagehiro & Stanton, 1985;Kerr et al, 1976;Nagel, 1979;Ostrom, Werner, & Saks, 1978;Simon, 1970;Thomas & Hogue, 1976). Wells proposed, instead, that people occasionally engage in fact-to-evidence reasoning-that is, Wells argued, "In order for evidence to have a significant impact on people's verdict preferences, one's hypothetical belief about the ultimate fact must affect one's belief about the evidence" (p. 746).…”
mentioning
confidence: 97%
“…To many jurors "jury instructions are like foreign movies without subtitles" (Wald 1993:111, quoting Stephen Adler). Verbal instructions have misled subjects in mock juries (Kagehiro and Stanton 1985). Estimates of what "beyond a reasonable doubt" meant ranged from 51 to 91% of certainty (Hastie 1993:101-108).…”
Section: Violations Of the Rational Choice Benchmarkmentioning
confidence: 99%